Microstructure and properties of selected WC-cemented carbides manufactured by SPS method - Genga, Rodney Michael (My University, 2015)
The effects of spark plasma sintering (SPS), WC starting particle size (0.1-0.8 μm), NbC, TiC and Mo2C additions on the microstructure and mechanical properties of WC-Co and WC-Ni alloys were investigated. Spark plasma sintering has the main advantage of very high degrees of densification obtainable at low temperatures within short sintering times, preventing Ostwald ripening. Spark plasma sintered WC-0.5Cr3C2-10Co (wt%) and WC-9.3Ni (wt%) samples had finer WC grains with poorly distributed binder pools than similar liquid phase sintered (LPS) samples, resulting in higher hardness, lower fracture toughness (K1C) and transverse rupture strength (TRS). Although the SPS samples had smaller WC grains than the LPS samples, WC grains of up to 1μm occurred in the nano and ultrafine grades, due to coalescence of fine particles. High NbC additions (≥20 wt%) to WC-10Co (wt%) reduced the WC grain size, hardness, K1C, TRS and modulus of elasticity in all grades. The poor mechanical properties were attributed to the reduction of WC volume fraction, formation of the (Nb,W) solid solution and poor wetting of NbC by Co. Additions of 6.25 wt% TiC and 0.5-5 wt% Mo2C to the WC-9.3Ni (wt%) nano and ultrafine samples gave the finest WC grain sizes, due to good grain growth inhibition. Molybdenum carbide also improved the Ni binder distribution due to better wetting of WC by the Ni. The refined microstructure and improved Ni binder distribution, together with reduced binder amount (7 wt%) gave >20 GPa hardness, slight reduction in K1C, good modulus of elasticity and lower TRS. The abrasion wear resistance increased with reduced WC grain size and binder amount, explaining the significantly higher abrasion resistance of the SPS WC-5Mo2C-6.25TiC-7Ni (wt%) ultrafine and nano grades than the LPS samples. The LPS WC-9.3Ni sample, had higher abrasion wear resistance than the LPS WC-0.5Cr3C2-10Co (wt%) sample, because of the slightly lower binder content and the Ni binder’s better wear properties. The LPS samples had the highest thermal shock and impact resistance (higher TRS and K1C). The WC-0.5Cr3C2-5NbC-10Co (wt%) sample had a good hardness, from SPS and the addition of NbC and Cr3C2 grain growth inhibitors, as well as good K1C and TRS, from its high binder amount and good wetting of WC by Co. These resulted in a good combination of abrasion wear, thermal shock and impact resistance in the WC-0.5Cr3C2-5NbC-10Co (wt%) sample. The WC-5Mo2C-6.25TiC-7Ni (wt%) ultrafine grade sample had the lowest thermal shock and impact resistance because of its poor K1C and TRS.